The Effect of PFI Commitments on Local Authority Finances - Margaret Cuthber t, Margaret Cuthbert Jim Cuthbert (2011)
This article looks at the question of how the unitary charge payments of PFI contracts are indexed to allow for inflation over the 25 to 30 year life of the contract. This follows a number of articles and reports in which we have considered other aspects of PFI: among these, for example, were analyses of financial projections, where it was shown that there were high returns to consortia (2008): analyses of PFI contracts, showing inadequacies in the public sector approach, (2010a): and a study of the bidding process, indicating restricted competition, (2010b).